PP material for automobile bumper

By designing and optimizing the formula in the PP material for automobile bumpers, using homopolymer and copolymerized PP compounding, and adding modified fillers and POE, the existing PP material has been solved by poor impact resistance and poor heat resistance. The problem is good, and high fluidity and excellent mechanical properties are achieved.

CN119463365APending Publication Date: 2025-02-18JIANGSU RUIWEN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411789851.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing PP materials for automobile bumpers have problems such as poor impact resistance and poor heat resistance and scratch resistance.

Method used

Through formulation design optimization, homopolymerized PP and copolymerized PP are used for compounding, and modified fillers, POE and other components are added. The side feeding melt extrusion process is used to form a "core-shell structure" and a sheet-like structure to improve the material mechanical and thermal properties.

Benefits of technology

It achieves high flowability, good impact resistance, heat resistance and scratch resistance, and has excellent processing performance and appearance performance, meeting the requirements of automobile bumpers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 5IXMGVLMHEBK83OBE21OTXJSNT2CYWOO4HTIM70E
    Figure 5IXMGVLMHEBK83OBE21OTXJSNT2CYWOO4HTIM70E
Patent Text Reader

Abstract

The invention belongs to the field of plastics. The invention relates to a PP material for an automobile bumper and a preparation method of the PP material. The PP material for the automobile bumper comprises the following raw materials in parts by weight: 88-97 parts of PP; 3 to 12 parts of POE (Polyolefin Elastomer); 1.0 to 3.0 parts of a modified filler; 2.0 to 5.0 parts of a modified filler I; 10 to 20 parts of a modified filler II; 0.1 to 1.0 part of an antioxidant; 0.2 to 0.8 part of a light stabilizer; 0.1 to 0.5 part of a lubricant; 0.5 to 2.0 parts of a scratch resistant agent; wherein the modified filler I and the modified filler II are self-made fillers; the components are respectively subjected to processes of filler pretreatment, mixing, extrusion and granulation, and a specific side charging process is utilized to prepare the composite material. The novel PP material for the automobile bumper effectively solves the problems of poor impact resistance, heat resistance and scratch resistance of the PP material for the automobile bumper in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a PP material for automobile bumper and a preparation method thereof. The invention belongs to the field of plastics. Background Art

[0002] Automobile bumpers have the functions of buffering collision impact, protecting vehicles and members, and decorating vehicles. In order to reduce automobile production costs and meet lightweight technical requirements, the materials used to produce bumpers have changed from early metal materials to engineering plastics with good strength, rigidity, and plasticity. Polypropylene has become the mainstream of engineering plastics used in bumper production due to its low cost, lightweight, and recyclable performance advantages.

[0003] The car bumper is a large-scale car exterior part, which is generally made by injection molding. Since the bumper is a large-scale thin-walled structural component with a large surface area and complex shape, while ensuring the balance of material rigidity and toughness, the material used to make the car bumper must have good fluidity to ensure smooth molding; good rigidity and no deformation, so that the product has a good and stable appearance, and high impact resistance to meet the use requirements.

[0004] On the premise of meeting the performance requirements, in order to make the bumper lighter, better performing and cheaper, the following requirements or performance indicators must be met: (1) Good weather resistance and heat resistance higher than 80-100℃; (2) Impact strength of 0.3-4J / cm 2 ; (3) Tensile strength reaches 20-40MPa; (4) Good molding and processing performance, easy to realize industrial production; (5) Good fluidity, the melt flow rate is preferably between 35-40g / 10min; (6) Good scratch resistance and wear resistance.

[0005] Therefore, it is necessary to design a special polypropylene material for automobile bumpers with high fluidity, high toughness and scratch resistance to meet the needs of the ever-changing automobile industry. Summary of the invention

[0006] The purpose of the present invention is to provide a new type of PP material for automobile bumper and its preparation method in view of the problems of poor impact resistance and poor heat resistance and scratch resistance of PP material for automobile bumper in the prior art. After formula design optimization, modified and compounded fillers used, and side-feeding melt extrusion granulation, the above problems can be effectively solved. The technical solution adopted by the present invention to solve its technical problems is: The present invention provides a PP material for automobile bumper, comprising the following raw materials in parts by weight: PP 88-97 copies; POE 3-12 copies; 1.0-3.0 parts of modified filler; Modified filler I 2.0-5.0 parts; Modified filler II 10-20 parts; Antioxidant 0.1-1.0 part; Light stabilizer 0.2-0.8 parts; Lubricant 0.1-0.5 parts; 0.5-2.0 parts of anti-scratch agent; Wherein, the modified filler is a silane-modified filler containing a carbon-carbon double bond; The filler is and the particle size is 2000-5000 mesh; The preparation method of the modified filler I comprises the following steps: S11, surface-modifying filler I with a silane coupling agent I containing a carbon-carbon double bond to obtain an intermediate product 1I; S12, mixing and granulating the intermediate product 1I, maleic anhydride, POE and DCP to obtain the target product, modified filler I; The particle size of the filler I is 2000-3000 mesh; as well as The preparation method of the modified filler II comprises the following steps: S21, free radical polymerization of a silane coupling agent II containing a carbon-carbon double bond, styrene, and maleic anhydride to obtain an intermediate product 2I; S22, coupling reaction of the intermediate product 2I and filler II to obtain a target product, i.e., modified filler II; The filler II has a lamellar structure and a particle size of 1000-3000 meshes.

[0007] Furthermore, the usage ratio of the filler I to the silane coupling agent I containing a carbon-carbon double bond is 1 g: 3.5-5.5 g; and The filler I is calcium carbonate, silicon dioxide or barium sulfate.

[0008] Further, The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g: 0.5-1.5g: 5-15g: 0.2g.

[0009] Further, The usage ratio of the carbon-carbon double bond-containing silane coupling agent II, styrene and maleic anhydride is 10g:40-60g:4-6g.

[0010] Further, the usage ratio of the intermediate product 2I and the filler II is 0.5-1.2 g: 1 g; and The lamellar structure is talcum powder.

[0011] Furthermore, the PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.0-3.0:1; and The melt index of the copolymer PP is 60-100 g / 10 min; the melt index of the homopolymer PP is 25-30 g / 10 min.

[0012] Furthermore, the melt index of the POE is 5-10 g / 10 min.

[0013] The present invention also provides a method for preparing a PP material for an automobile bumper, comprising the following steps: S31, mixing; POE and modified filler I are mixed evenly to obtain component I; other raw materials in the formula are mixed evenly to obtain component II; S32, extrusion; Component I in S31 is added from the main feeding port of the extruder, and component II is added from the side feeding port, and melt blended and extruded; S33, granulation; The melt in S32 is subjected to the steps of stranding, cooling and pelletizing to obtain PP material for automobile bumper.

[0014] Further, the extruder has a screw aspect ratio of 50-60:1 and a rotation speed of 300-400 rpm; and The temperatures of the screw sections of the extruder are 170-180°C in zone 1, 180-190°C in zone 2, 185-195°C in zone 3, 185-195°C in zone 4, 190-200°C in zone 5, 195-205°C in zone 6, 195-205°C in zone 7, 200-210°C in zone 8, 200-210°C in zone 9, 205-215°C in zone 10, 205-215°C in zone 11; and 200-210°C in zone 12.

[0015] Furthermore, the side feeding port is located in the third zone or the fourth zone of the extruder.

[0016] Beneficial effects of the present invention: (1) The present invention provides a PP material for automobile bumper, wherein the PP in the formula system is compounded with homopolymer PP and copolymer PP. First, homopolymer PP has high crystallinity, thus having high heat resistance and scratch resistance; while the regularity of the molecular chain of copolymer PP decreases, thus having good impact resistance; the compounding of the two can have both high heat resistance and scratch resistance, and also have good impact resistance; second, compounding and blending PP with different melt indexes is conducive to balancing the processability and appearance performance of the product.

[0017] (2) The present invention provides a PP material for automobile bumpers, wherein the fillers in the formula system include modified fillers, modified fillers I, and modified fillers II. Among them, the modified filler is a silane coupling agent containing carbon-carbon double bonds that is surface-modified; the modified filler I is an inorganic filler embedded in copolymers such as POE and maleic anhydride; and the modified filler II is a structure in which the surface of a lamellar inorganic filler is modified by copolymers such as styrene and maleic anhydride. First, the modified filler has multiple carbon-carbon double bond structures after surface treatment, has a cross-linking effect, can improve heat resistance, scratch resistance and other properties, and has a reinforcing effect; in addition, it can be used as a heterogeneous nucleating agent for PP crystallization to promote the crystallization of PP; second, the modified filler I is an embedded structure such as POE, has excellent dispersibility, and when it is melt-blended and extruded with POE, it can increase the overall volume of POE to form a "core-shell structure" to improve the toughening effect of POE; it also has the effect of increasing the rigidity of the material; third, the modified filler II is Surface modification structures such as styrene and maleic anhydride have the highest proportion of styrene structural units in the molecular chain structure, and the organic chain structure cannot effectively encapsulate the filler. Therefore, the structure is similar to an organic chain as the main body and an inorganic filler as a "side chain" structure. Therefore, the structure has a larger molecular chain entanglement and a lamellar structure slip space in the PP material, and has better rigidity, scratch resistance, wear resistance, impact resistance, heat resistance and other mechanical and thermal properties; Fourth, the above three modified fillers have body shape and lamellar structure respectively, and also have better low shrinkage and other properties.

[0018] (3) The present invention provides a PP material for automobile bumper. The POE in the formula system is a toughening agent, which has the function of promoting molding processing and improving the impact resistance of the product; and it is pre-blended with the modified filler I to effectively improve the toughening effect and also has a reinforcing effect.

[0019] (4) The present invention provides a method for preparing PP material for automobile bumper. Through the side feeding melt extrusion process, component I formed by modified filler I and POE is added from the main feeding port for effective blending and melting, and component II enters the screw through the side feeding port, and is sheared, dispersed, melted, and extruded by the ultra-long aspect ratio screw. On the one hand, the time for component I to form a "core-shell structure" is reserved; on the other hand, the over-shear oxidation of PP is reduced, resulting in a wide molecular weight distribution, and deterioration of mechanical properties and crystallization properties; in addition, the long aspect ratio also has the effect of fully mixing and melting other components, effectively improving the dispersibility of each component, thereby improving mechanical properties, etc. DETAILED DESCRIPTION

[0020] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0021] The purpose of the present invention is to develop a high-performance PP material for automobile bumpers in view of the problems of poor impact resistance, heat resistance and scratch resistance of PP materials for automobile bumpers in the prior art. The idea of ​​realization is: firstly, PP with different melt indexes are blended to obtain a resin material with excellent mechanical and thermal properties; then, in order to improve the impact resistance, POE is added as a toughening agent and suitable fillers are added to improve the heat resistance and scratch resistance, thereby obtaining the final product. To achieve the above purpose: the present invention prepares three kinds of modified fillers, namely modified filler, modified filler I and modified filler II; firstly, the preparation of the modified filler is silane coupling of conventional fillers, and the particle size is optimized, which can be used as a crosslinking agent and a nucleating agent to improve the performance; secondly, the modified filler I is designed, and the filler I treated with a silane coupling agent is grafted and copolymerized with POE and maleic anhydride by melt extrusion, so that the filler is embedded in the POE structure to form a similar "core-shell structure"; and it is premixed with the POE resin in the formula, which can exert the maximum toughening effect achieved by limited POE, and has Synergistic, toughening and reinforcing effects; thirdly, the modified filler II is structurally designed, first preparing a copolymer structure containing silane coupling agent, styrene and maleic anhydride, and then coupling it with lamellar talcum powder for preparation; because talcum powder has a multi-layer structure, the lamellar layers can slip, and after coupling it with the copolymer, styrene, as a large amount of component, makes the coupling process have a vacancy effect, reserving a large relative slip space, and further improving the ductility; at the same time, the rigid structure of styrene can improve heat resistance, scratch resistance, wear resistance, etc.; in addition, talcum powder has excellent heat resistance, low shrinkage, rigidity and other advantages and is effectively applied. The above three fillers work synergistically, the above fillers are placed in the formula system, and are extruded and granulated by an ultra-long aspect ratio twin screw and a side feeding process to obtain the target material, which can solve the problems of poor impact resistance, heat resistance and scratch resistance of PP materials for automobile bumpers. The embodiments of the present invention are as follows: The embodiment of the present invention provides a PP material for automobile bumper, comprising the following raw materials in parts by weight: PP 88-97 copies; POE 3-12 copies; 1.0-3.0 parts of modified filler; Modified filler I 2.0-5.0 parts; Modified filler II 10-20 parts; Antioxidant 0.1-1.0 part; Light stabilizer 0.2-0.8 parts; Lubricant 0.1-0.5 parts; 0.5-2.0 parts of anti-scratch agent; Wherein, the modified filler is a silane-modified filler containing a carbon-carbon double bond; The preparation method of the modified filler is as follows: Add filler and silane containing carbon-carbon double bonds to ethanol A, ultrasonically oscillate for 0.5 h, let stand at room temperature for 2 h, react at 60°C for 6 h, filter, take out insoluble matter, rinse with ethanol B for 3 times, and then dry the insoluble matter at 60°C for 12 h to obtain intermediate product III.

[0022] The usage ratio of the filler, the silane coupling agent and the alcohol solvent is 1g:4.5g:80mL.

[0023] The filler may be calcium carbonate, silicon dioxide or barium sulfate; and the particle size is 2000-5000 mesh; and calcium carbonate is preferred.

[0024] The silane coupling agent containing a carbon-carbon double bond may be a vinyl silane coupling agent or an acryloxy silane coupling agent; The vinyl silane coupling agent may be KH151, KH171, KH172 or KH173, etc., and KH171 is preferred.

[0025] The acryloxysilane coupling agent may be KH570, KH571, KH670, GX572, etc., and KH570 is preferred.

[0026] The preparation method of the modified filler I comprises the following steps: S11, add filler I and silane coupling agent I containing carbon-carbon double bonds to ethanol A, ultrasonically oscillate for 0.5 h, stand at room temperature for 2 h, react at 40-60° C. for 6-10 h, filter, take out insoluble matter, rinse with ethanol B three times, and dry the insoluble matter at 60° C. for 12 h to obtain intermediate product 1I.

[0027] The usage ratio of the filler I, the silane coupling agent I containing a carbon-carbon double bond, and the ethanol A is 1 g: 3.5-5.5 g: 80 mL.

[0028] The particle size of the filler I is 2000-3000 mesh; The filler I is calcium carbonate, silicon dioxide or barium sulfate; The silane coupling agent I containing a carbon-carbon double bond may be a vinyl silane coupling agent or an acryloxy silane coupling agent; The vinyl silane coupling agent may be KH151, KH171, KH172 or KH173, etc., and KH171 is preferred.

[0029] The acryloxysilane coupling agent may be KH570, KH571, KH670, GX572, etc., and KH570 is preferred.

[0030] S12, adding the intermediate product 1I, maleic anhydride and DCP to acetone, ultrasonically dispersing for 2 hours, adding to POE, mixing evenly, drying at room temperature, adding the mixture to a twin-screw extruder for mixing and granulation to obtain the target product, modified filler I.

[0031] The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g: 0.5-1.5g: 5-15g: 0.2g.

[0032] The temperatures of the twin-screw extruder are 175° C. in zone 1, 180° C. in zone 2, 185° C. in zone 3, 195° C. in zone 4, and 205° C. in zone 5, respectively; the die is 200° C.; and the screw speed is 200 rpm.

[0033] The preparation method of the modified filler II comprises the following steps: S21, add silane coupling agent II containing carbon-carbon double bonds, styrene, maleic anhydride and initiator AIBN to N,N-dimethylformamide, heat to 80-90°C, and stir for 6-10h; after the reaction is completed, distill under reduced pressure and vacuum dry at 60°C for 6h to obtain intermediate product 2I.

[0034] The usage ratio of the carbon-carbon double bond-containing silane coupling agent II, styrene, maleic anhydride and initiator AIBN is 10g:40-60g:4-6g:0.5g.

[0035] The silane coupling agent II containing a carbon-carbon double bond may be a vinyl silane coupling agent or an acryloxy silane coupling agent; The vinyl silane coupling agent may be KH151, KH171, KH172 or KH173, etc., and KH171 is preferred.

[0036] The acryloxysilane coupling agent may be KH570, KH571, KH670, GX572, etc., and KH570 is preferred.

[0037] S22, add the intermediate product 2I and filler II to ethanol A, ultrasonically oscillate for 0.5 h, let stand at room temperature for 2 h, react at 50-70°C for 1-2 h, filter, take the insoluble matter, rinse with ethanol B for 3 times, and then dry the insoluble matter at 60°C for 12 h to obtain the target product, i.e., modified filler II.

[0038] The usage ratio of the intermediate product 2I, filler II, and ethanol A is 0.5-1.2 g: 1 g: 50 mL; The filler II has a lamellar structure and a particle size of 1000-3000 meshes.

[0039] The lamellar structure is talcum powder.

[0040] The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.0-3.0:1; The melt index of the copolymer PP is 60-100g / 10min; when the melt index is less than 60 g / 10min, the molecular weight is large and the processing and molding is difficult; and when the melt index is greater than 100 g / 10min, the molecular weight is small and the mechanical properties are low, which affects the product quality; therefore, the copolymer PP can be K7760H (Yanshan Petrochemical), M60T (Zhenhai Refining and Chemical), EPL31UA (Iran JPC), EP640V (South Korea Dalin), etc.; from the easy acquisition of raw materials, K7760H (Yanshan Petrochemical) is preferred in the embodiments of the present invention, and the copolymer PP described in the following embodiments of the present invention is K7760H. The melt index of the homopolymer PP is 25-30g / 10min; it can be Z30S (Fushun Petrochemical), etc., and the homopolymer PP described in the following embodiments of the present invention is Z30S.

[0041] The POE has a melt index of 5-10 g / 10 min and may be ENGAGE 8207 (Dow Chemical) or LC670 (LG, South Korea). In addition, the POE described in the following embodiments of the present invention is ENGAGE 8207.

[0042] The antioxidant is a mixture of hindered phenols and phosphites in a mass ratio of 1 / 2. In addition, the antioxidant described in the following embodiments of the present invention is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1 / 2.

[0043] The light stabilizer is a mixture of hindered amines and ultraviolet absorbers in a mass ratio of 1 / 2. In addition, the light stabilizer in the following embodiments of the present invention is a mixture of UV-770 and UV-41 in a mass ratio of 1 / 2.

[0044] The lubricant is erucamide, ethylenebisfatty acid amide, etc.; and, the lubricant in the following embodiments of the present invention is erucamide.

[0045] The scratch-resistant agent is a silicone masterbatch, etc. The scratch-resistant agent described in the following embodiments of the present invention is a silicone masterbatch, with a brand of MB50-001.

[0046] The embodiment of the present invention also provides a method for preparing a PP material for an automobile bumper, comprising the following steps: S31, mixing; POE and modified filler I were added into a mixer, and stirred at a stirring rate of 300 r / min for 30 min to obtain component I; other raw materials in the formula were stirred at a stirring rate of 800 r / min for 10 min to obtain component II; S32, extrusion; Component I in S31 is added from the main feeding port of the extruder, and component II is added from the side feeding port, and melt blended and extruded; The extruder has a screw length-to-diameter ratio of 50-60:1 and a rotation speed of 300-400 rpm; The temperatures of the screw sections of the extruder are 170-180°C in zone 1, 180-190°C in zone 2, 185-195°C in zone 3, 185-195°C in zone 4, 190-200°C in zone 5, 195-205°C in zone 6, 195-205°C in zone 7, 200-210°C in zone 8, 200-210°C in zone 9, 205-215°C in zone 10, 205-215°C in zone 11; and 200-210°C in zone 12.

[0047] The side feed port is located in the third zone or the fourth zone of the extruder.

[0048] S33, granulation; The melt in S32 is subjected to stranding, water cooling and pelletizing to obtain PP material for automobile bumper.

[0049] In order to further understand the present invention, a PP material for automobile bumper provided by the present invention is described in detail below in conjunction with specific embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0050] A PP material for automobile bumper, comprising the following raw materials in parts by weight: PP 92 copies; POE 8 copies; 1.8 parts of modified filler; Modified filler I 4.0 parts; Modified filler II 15 parts; 0.5 parts of antioxidant; Light stabilizer 0.4 parts; 0.3 parts of lubricant; 1.5 parts of anti-scratch agent; Wherein, the modified filler is calcium carbonate treated with KH171 and has a particle size of 4000 mesh.

[0051] The preparation method of the modified filler I comprises the following steps: S11, calcium carbonate and silane coupling agent KH171 were added to ethanol A, ultrasonically oscillated for 0.5 h, allowed to stand at room temperature for 2 h, reacted at 50 ° C for 7.5 h, filtered, and the insoluble matter was taken. After rinsing with ethanol B for 3 times, the insoluble matter was dried at 60 ° C for 12 h to obtain the intermediate product 1I.

[0052] The usage ratio of calcium carbonate, silane coupling agent KH171 and ethanol A is 1g:4.5g:80mL.

[0053] The calcium carbonate particle size is 2500 mesh; Its infrared data are as follows: 1625cm -1 :-C=C- exists; 1383cm -1 :-CO- exists; 1109 cm -1 、798cm -1 :-Si-O- exists; 712cm -1 :-Ca-O- exists.

[0054] S12, adding the intermediate product 1I, maleic anhydride and DCP to acetone, ultrasonically dispersing for 2 hours, adding to POE, mixing evenly, drying at room temperature, adding the mixture to a twin-screw extruder for mixing and granulation to obtain the target product, modified filler I.

[0055] The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g:1.0g:10g:0.2g.

[0056] The temperatures of the twin-screw extruder are 175° C. in zone 1, 180° C. in zone 2, 185° C. in zone 3, 195° C. in zone 4, and 205° C. in zone 5, respectively; the die is 200° C.; and the screw speed is 200 rpm.

[0057] Its infrared data are as follows: 2904cm -1 :-CC-exists; 1786cm -1 :-C=O (anhydride) exists; 1635cm -1 :-C=C- does not exist; 1383cm -1 :-CO- exists; 1109 cm -1 、798cm -1 :-Si-O- exists; 712cm -1 :-Ca-O- exists.

[0058] The preparation method of the modified filler II comprises the following steps: S21, add silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN to N,N-dimethylformamide, heat to 85°C, and stir for 8 hours; after the reaction is completed, distill under reduced pressure and vacuum dry at 60°C for 6 hours to obtain the intermediate product 2I.

[0059] The usage ratio of the silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN is 10g:50g:5g:0.5g.

[0060] Its infrared data are as follows: 3011cm -1 、1595cm -1、1498cm -1 : Benzene ring exists; 1786cm -1 :-C=O (anhydride) exists; 1622cm -1 :-C=C- does not exist; 1109 cm -1 、798cm -1 :-Si-O- exists.

[0061] S22, add the intermediate product 2I and talcum powder to ethanol A, ultrasonically oscillate for 0.5 h, let stand at room temperature for 2 h, react at 60°C for 1.5 h, filter, take the insoluble matter, rinse with ethanol B for 3 times, and dry the insoluble matter at 60°C for 12 h to obtain the target product, i.e., modified filler II.

[0062] The usage ratio of the intermediate product 2I, talcum powder and ethanol A is 1.0 g: 1 g: 50 mL; The particle size of the talcum powder is 2000 meshes.

[0063] Its infrared data are as follows: 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1786cm -1 :-C=O (anhydride) exists; 1622cm -1 :-C=C- does not exist; 1109 cm -1 、798cm -1 :-Si-O- exists and is enhanced; 621cm -1 :-Mg-O- exists.

[0064] The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.5:1.

[0065] The embodiment of the present invention also provides a method for preparing a PP material for an automobile bumper, comprising the following steps: S31, mixing; POE and modified filler I were added into a mixer, and stirred at a stirring rate of 300 r / min for 30 min to obtain component I; other raw materials in the formula were stirred at a stirring rate of 800 r / min for 10 min to obtain component II; S32, extrusion; Component I in S31 is added from the main feeding port of the extruder, and component II is added from the side feeding port, and melt blended and extruded; The extruder has a screw length-to-diameter ratio of 56:1 and a rotation speed of 338 rpm; The temperatures of the screw sections of the extruder are 175°C in zone 1, 185°C in zone 2, 190°C in zone 3, 192°C in zone 4, 195°C in zone 5, 199°C in zone 6, 202°C in zone 7, 205°C in zone 8, 208°C in zone 9, 210°C in zone 10, 210°C in zone 11, and 205°C in zone 12.

[0066] The side feed port is located in the third zone of the extruder.

[0067] S33, granulation; The melt in S32 is subjected to stranding, water cooling and pelletizing to obtain PP material for automobile bumper.

[0068] A PP material for automobile bumper, comprising the following raw materials in parts by weight: PP 97 copies; POE 3 copies; 1.0 part of modified filler; Modified filler I 5.0 parts; Modified filler II 20 parts; 1.0 part of antioxidant; Light stabilizer 0.2 parts; 0.5 parts of lubricant; 0.5 parts of anti-scratch agent; Wherein, the modified filler is calcium carbonate treated with KH171 and has a particle size of 4000 mesh.

[0069] The preparation method of the modified filler I comprises the following steps: S11, calcium carbonate and silane coupling agent KH171 were added to ethanol A, ultrasonically oscillated for 0.5 h, allowed to stand at room temperature for 2 h, reacted at 40 °C for 10 h, filtered, the insoluble matter was taken, rinsed with ethanol B for 3 times, and then the insoluble matter was dried at 60 °C for 12 h to obtain the intermediate product 1I.

[0070] The usage ratio of calcium carbonate, silane coupling agent KH171 and ethanol A is 1g:5.5g:80mL.

[0071] The calcium carbonate particle size is 2000 mesh; S12, adding the intermediate product 1I, maleic anhydride and DCP to acetone, ultrasonically dispersing for 2 hours, adding to POE, mixing evenly, drying at room temperature, adding the mixture to a twin-screw extruder for mixing and granulation to obtain the target product, modified filler I.

[0072] The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g:1.5g:15g:0.2g.

[0073] The temperatures of the twin-screw extruder are 175° C. in zone 1, 180° C. in zone 2, 185° C. in zone 3, 195° C. in zone 4, and 205° C. in zone 5, respectively; the die is 200° C.; and the screw speed is 200 rpm.

[0074] The preparation method of the modified filler II comprises the following steps: S21, add silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN to N,N-dimethylformamide, heat to 80°C, and stir for 10 hours; after the reaction is completed, distill under reduced pressure and vacuum dry at 60°C for 6 hours to obtain the intermediate product 2I.

[0075] The usage ratio of the silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN is 10g:50g:5g:0.5g.

[0076] S22, add the intermediate product 2I and talcum powder to ethanol A, ultrasonically oscillate for 0.5 h, let stand at room temperature for 2 h, react at 70°C for 1 h, filter, take the insoluble matter, rinse with ethanol B for 3 times, and dry the insoluble matter at 60°C for 12 h to obtain the target product, i.e., modified filler II.

[0077] The usage ratio of the intermediate product 2I, talcum powder and ethanol A is 1.0 g: 1 g: 50 mL; The particle size of the talcum powder is 2000 meshes.

[0078] The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.5:1.

[0079] The embodiment of the present invention also provides a method for preparing a PP material for an automobile bumper, comprising the following steps: S31, mixing; POE and modified filler I were added into a mixer, and stirred at a stirring rate of 300 r / min for 30 min to obtain component I; other raw materials in the formula were stirred at a stirring rate of 800 r / min for 10 min to obtain component II; S32, extrusion; Component I in S31 is added from the main feeding port of the extruder, and component II is added from the side feeding port, and melt blended and extruded; The extruder has a screw length-to-diameter ratio of 60:1 and a rotation speed of 306 rpm; The temperatures of the screw sections of the extruder are 180°C in zone 1, 190°C in zone 2, 195°C in zone 3, 195°C in zone 4, 200°C in zone 5, 203°C in zone 6, 205°C in zone 7, 209°C in zone 8, 210°C in zone 9, 215°C in zone 10, 215°C in zone 11, and 210°C in zone 12.

[0080] The side feed port is located in the fourth zone of the extruder.

[0081] S33, granulation; The melt in S32 is subjected to stranding, water cooling and pelletizing to obtain PP material for automobile bumper.

[0082] A PP material for automobile bumper, comprising the following raw materials in parts by weight: PP 88 copies; POE 12 copies; 3.0 parts of modified filler; Modified filler I 2.0 parts; Modified filler II 10 parts; Antioxidant 0.1 part; Light stabilizer 0.8 parts; Lubricant 0.1 part; 2.0 parts of anti-scratch agent; Wherein, the modified filler is calcium carbonate treated with KH171 and has a particle size of 4000 mesh.

[0083] The preparation method of the modified filler I comprises the following steps: S11, calcium carbonate and silane coupling agent KH171 were added to ethanol A, ultrasonically oscillated for 0.5 h, allowed to stand at room temperature for 2 h, reacted at 60 ° C for 6 h, filtered, and the insoluble matter was taken out. After rinsing with ethanol B for 3 times, the insoluble matter was dried at 60 ° C for 12 h to obtain the intermediate product 1I.

[0084] The usage ratio of calcium carbonate, silane coupling agent KH171 and ethanol A is 1g:3.5g:80mL.

[0085] The calcium carbonate particle size is 3000 mesh; S12, adding the intermediate product 1I, maleic anhydride and DCP to acetone, ultrasonically dispersing for 2 hours, adding to POE, mixing evenly, drying at room temperature, adding the mixture to a twin-screw extruder for mixing and granulation to obtain the target product, modified filler I.

[0086] The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g:0.5g:5g:0.2g.

[0087] The temperatures of the twin-screw extruder are 175° C. in zone 1, 180° C. in zone 2, 185° C. in zone 3, 195° C. in zone 4, and 205° C. in zone 5, respectively; the die is 200° C.; and the screw speed is 200 rpm.

[0088] The preparation method of the modified filler II comprises the following steps: S21, add silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN to N,N-dimethylformamide, heat to 90°C, and stir for 6 hours; after the reaction is completed, distill under reduced pressure and vacuum dry at 60°C for 6 hours to obtain the intermediate product 2I.

[0089] The usage ratio of the silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN is 10g:50g:5g:0.5g.

[0090] S22, add the intermediate product 2I and talcum powder to ethanol A, ultrasonically oscillate for 0.5 h, let stand at room temperature for 2 h, react at 50°C for 2 h, filter, take the insoluble matter, rinse with ethanol B for 3 times, and then dry the insoluble matter at 60°C for 12 h to obtain the target product, i.e., modified filler II.

[0091] The usage ratio of the intermediate product 2I, talcum powder and ethanol A is 1.0 g: 1 g: 50 mL; The particle size of the talcum powder is 2000 meshes.

[0092] The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.5:1.

[0093] The embodiment of the present invention also provides a method for preparing a PP material for an automobile bumper, comprising the following steps: S31, mixing; POE and modified filler I were added into a mixer, and stirred at a stirring rate of 300 r / min for 30 min to obtain component I; other raw materials in the formula were stirred at a stirring rate of 800 r / min for 10 min to obtain component II; S32, extrusion; Component I in S31 is added from the main feeding port of the extruder, and component II is added from the side feeding port, and melt blended and extruded; The extruder has a screw length-to-diameter ratio of 50:1 and a rotation speed of 391 rpm; The temperatures of the screw sections of the extruder are 170°C in zone 1, 180°C in zone 2, 185°C in zone 3, 188°C in zone 4, 190°C in zone 5, 195°C in zone 6, 195°C in zone 7, 200°C in zone 8, 203°C in zone 9, 205°C in zone 10, 205°C in zone 11; and 200°C in zone 12.

[0094] The side feed port is located in the third zone of the extruder.

[0095] S33, granulation; The melt in S32 is subjected to stranding, water cooling and pelletizing to obtain PP material for automobile bumper.

[0096] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2:1.

[0097] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 3:1.

[0098] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The modified filler is calcium carbonate (5000 mesh) treated with silane coupling agent KH570.

[0099] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The modified filler is calcium carbonate (2000 mesh) treated with silane coupling agent KH570.

[0100] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The calcium carbonate treated with KH171 in the modified filler I was replaced with silica treated with KH570.

[0101] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The calcium carbonate treated with KH171 in the modified filler I was replaced with barium sulfate treated with KH570.

[0102] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, In the preparation method of the inorganic filler II, in step S21, The usage ratio of the silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN is 10g:40g:4g:0.5g.

[0103] In step S22, The usage ratio of the intermediate product 2I, talcum powder and ethanol A is 0.5 g: 1 g: 50 mL; The particle size of the talcum powder is 3000 meshes.

[0104] The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, In the preparation method of the inorganic filler II, in step S21, The usage ratio of the silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN is 10g:60g:6g:0.5g.

[0105] In step S22, The usage ratio of the intermediate product 2I, talcum powder and ethanol A is 1.2 g: 1 g: 50 mL; The particle size of the talcum powder is 1000 mesh.

[0106] The following comparative examples are compared with specific embodiment 1: Comparative Example 1 The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 0:1; that is, no copolymer PP is added.

[0107] Comparative Example 2 The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.5:0; that is, no homopolymer PP is added.

[0108] Comparative Example 3 The rest is the same as in Example 1, except that: A PP material for automobile bumper, No modified fillers were added to the formulation.

[0109] Comparative Example 4 The rest is the same as in Example 1, except that: A PP material for automobile bumper, No modified filler I was added to the formulation.

[0110] Comparative Example 5 The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, In the preparation method of the modified filler I, step S12 is not performed; that is, POE embedding is not performed.

[0111] Comparative Example 6 The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, In the preparation method of the modified filler I, in step S12, The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g:0g:10g:0.2g; that is, no maleic anhydride is added.

[0112] Comparative Example 7 The rest is the same as in Example 1, except that: A PP material for automobile bumper, No modified filler II was added to the formulation.

[0113] Comparative Example 8 The rest is the same as in Example 1, except that: A PP material for automobile bumper, The modified filler II is talc powder treated with KH171.

[0114] Comparative Example 9 The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, In the preparation method of the modified filler II, in step S21, The usage ratio of the silane coupling agent KH171, styrene, maleic anhydride and initiator AIBN is 10g:0g:5g:0.5g; that is, no styrene is added.

[0115] Comparative Example 10 The rest is the same as in Example 1, except that: In a PP material formula for automobile bumper, The particle sizes of the filler, filler I and filler II in the modified filler, modified filler I and modified filler II are all 800 meshes.

[0116] Comparative Example 11 The rest is the same as in Example 1, except that: A PP material for automobile bumper, No anti-scratch agents were added to the formulation.

[0117] Comparative Example 12 The rest is the same as in Example 1, except that: A method for preparing PP material for automobile bumper, in step S32, All raw materials are added from the main feeding port for extrusion.

[0118] The PP materials for automobile bumpers prepared in the embodiments of the present invention and the comparative examples were respectively measured and injection molded into standard specimens, and tested according to the standards. The results are shown in Table 1.

[0119] First, it can be concluded from Examples 1-11 in Table 1 that the PP material for automobile bumper of the present invention has excellent mechanical properties and thermal properties; specifically, it has excellent impact resistance, heat resistance, and scratch resistance; which is reflected in high notched impact strength, heat deformation temperature and low lightness.

[0120] It can be observed from Example 1 and Comparative Examples 1-2 that the PP material for automobile bumper in the present invention uses homopolymer PP and copolymer PP, which have a synergistic effect and improve the mechanical properties and thermal properties; it can be observed from Example 1 and Comparative Example 3 that the small-size structural filler has the effect of improving the mechanical properties and heat resistance after being treated with a silane coupling agent, which may be due to the fact that the small-size structure can promote PP crystallization and improve the performance; at the same time, its notched impact strength is not significantly reduced, because it has the effect of a cross-linking agent after being treated with a silane coupling agent, which increases the local cross-linking degree and has a chain extension effect; it can be observed from Example 1 and Comparative Examples 4-6 that the POE-embedded modified filler I has a synergistic effect of expanding the volume content of POE, which can effectively improve the impact resistance; it also has a certain reinforcing effect; from Example From Example 1 and Comparative Examples 7-9, it can be observed that the lamellar talc powder has excellent impact resistance, heat resistance and scratch resistance after being modified by silane, styrene and maleic anhydride copolymer; from Example 1 and Comparative Example 10, it can be observed that the appropriate particle size has a positive significance for the comprehensive performance of the material; from Example 1 and Comparative Example 11, it can be observed that the scratch resistance agent is of great significance to improving the scratch resistance of the material; at the same time, the modified filler II can act synergistically to improve the scratch resistance; from Example 1 and Comparative Example 12, it can be observed that the side feeding process (reducing the over-shear oxidation of PP, resulting in a wide molecular weight distribution, deterioration of mechanical properties and crystallization properties, and the time for the modified filler I in component I to melt blend with POE to form a coating structure) plays an important role in improving the comprehensive performance of the material.

[0121] In summary, the PP material for automobile bumper of the present invention has excellent appearance, excellent impact resistance, heat resistance and scratch resistance through formula design and process design optimization, and has great practical significance.

[0122] The test method is as follows: (1) Melt index: Test temperature: 230 °C, nominal load: 2.16 kg.

[0123] (2) Tensile strength: tested according to the method described in GB / T1040.2-2006; the tensile rate is 50 mm / min.

[0124] (3) Elongation at break: Tested according to the method described in GB / T1040.2-2006; the tensile rate is 50 mm / min.

[0125] (4) Notched impact strength: tested according to the method described in GB / T 1843.1-2008.

[0126] (5) Heat deformation temperature: Tested in accordance with the method described in GB / T 1634.2-2004; using 0.45 MPa bending stress B method.

[0127] (6) Molding shrinkage: Tested according to the method described in ISO 294-4-2007.

[0128] (7) Scratch resistance: Tested according to the method described in PV3952.

[0129] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A PP material for automobile bumper, characterized in that: The invention comprises the following raw materials in parts by weight: PP 88-97 copies; POE 3-12 copies; 1.0-3.0 parts of modified filler; Modified filler I 2.0-5.0 parts; Modified filler II 10-20 parts; Antioxidant 0.1-1.0 part; Light stabilizer 0.2-0.8 parts; Lubricant 0.1-0.5 parts; 0.5-2.0 parts of anti-scratch agent; Wherein, the modified filler is a silane-modified filler containing a carbon-carbon double bond; The filler particle size is 2000-5000 mesh; The preparation method of the modified filler I comprises the following steps: S11, surface-modifying filler I with a silane coupling agent I containing a carbon-carbon double bond to obtain an intermediate product 1I; S12, mixing and granulating the intermediate product 1I, maleic anhydride, POE and DCP to obtain the target product, modified filler I; The particle size of the filler I is 2000-3000 mesh; as well as The preparation method of the modified filler II comprises the following steps: S21, free radical polymerization of a silane coupling agent II containing a carbon-carbon double bond, styrene, and maleic anhydride to obtain an intermediate product 2I; S22, coupling reaction of the intermediate product 2I and filler II to obtain a target product, i.e., modified filler II; The filler II has a lamellar structure and a particle size of 1000-3000 meshes.

2. The PP material for automobile bumper according to claim 1, characterized in that: The usage ratio of the filler I to the silane coupling agent I containing a carbon-carbon double bond is 1 g:3.5-5.5 g; and The filler I is calcium carbonate, silicon dioxide or barium sulfate.

3. The PP material for automobile bumper according to claim 1, characterized in that: The usage ratio of the intermediate product 1I, maleic anhydride, POE and DCP is 10g: 0.5-1.5g: 5-15g: 0.2g.

4. The PP material for automobile bumper according to claim 1, characterized in that: The usage ratio of the carbon-carbon double bond-containing silane coupling agent II, styrene and maleic anhydride is 10g:40-60g:4-6g.

5. The preparation method according to claim 1, characterized in that: The usage ratio of the intermediate product 2I and the filler II is 0.5-1.2 g: 1 g; and The lamellar structure is talcum powder.

6. The PP material for automobile bumper according to claim 1, characterized in that: The PP is a mixture of copolymer PP and homopolymer PP in a mass ratio of 2.0-3.0:1; and The melt index of the copolymer PP is 60-100 g / 10 min; the melt index of the homopolymer PP is 25-30 g / 10 min.

7. The PP material for automobile bumper according to claim 1, characterized in that: The melt index of the POE is 5-10 g / 10 min.

8. A method for preparing PP material for automobile bumper, characterized in that: The following steps are involved: S31, mixing; POE and modified filler I are mixed evenly to obtain component I; other raw materials in the formula are mixed evenly to obtain component II; S32, extrusion; Component I in S31 is added from the main feeding port of the extruder, and component II is added from the side feeding port, and melt blended and extruded; S33, granulation; The melt in S32 is subjected to the steps of stranding, cooling and pelletizing to obtain PP material for automobile bumper.

9. The preparation method according to claim 8, characterized in that: The extruder has a screw length-to-diameter ratio of 50-60:1 and a rotation speed of 300-400 rpm; and The temperatures of the screw sections of the extruder are 170-180°C in zone 1, 180-190°C in zone 2, 185-195°C in zone 3, 185-195°C in zone 4, 190-200°C in zone 5, 195-205°C in zone 6, 195-205°C in zone 7, 200-210°C in zone 8, 200-210°C in zone 9, 205-215°C in zone 10, 205-215°C in zone 11; and 200-210°C in zone 12.

10. The preparation method according to claim 8, characterized in that: The side feed port is located in the third zone or the fourth zone of the extruder.